Analysis Of Passenger Perception On Ferry Port Service Of Mengkapan At Siak District, Riau Province Using Importance Performance Analysis - Hartanto Hartanto; Kodrat Alam; Trissa Dhea (IWTJ : International Water Transport Journal, 2019)
The Ferries Port of Mengkapan, Apit River, Siak District, Riau Province. The port plays an important role in improving the economy, particularly the field of transport for the local population. Based on observations in the field, there are some services that have not run well, soservice users were dissatisfied and uncomfortable while in The Ferries Port of Mengkapan. The method used to analyze the existing problems, ie Customer statisfaction Index and Importance Performance Analysis. Based on the analysis results obtained passenger satisfaction index of 43.9%, and there are nine service attributes that are in quadrant I, which should be improved and enhanced. The suggestions for the Port Authority, namely: (1) held Air Conditioner (AC) 4 pieces of 1.5 PK in the waiting room, repair the damaged chair, and clean the waiting room every day; (2) clean the toilet every day and ensure the availability of clear water; (3) conduct a complete information service facility; (4) expand the parking lot ready for loading and parking shuttle; (5) held a health facility; (6) held an emergency rescue facilities; (7) held CCTV; (8) improve the ticket purchasing process; (9) ensure timely arrival and departure of ships. Keywords: Analysis; Passenger Perception; Importance Performance Analysis.